HUBUNGAN PEMBERIAN STIMULASI OLEH ORANG TUA DENGAN PERKEMBANGAN BAHASA PADA ANAK USIA PRA SEKOLAH ( 3â5 TAHUN) DI TAMAN KANAK-KANAK AL-FATH PARE - Yektiningsih, Erwin; Martiningsih, Martiningsih; Mukayaroh, Anjaring (Jurnal AKP, 2010)
Preschool age-childrenis generation router asset then their growing must detection speciallylanguage because the language is communication elementary which that can support at other growing thenneeded is stimulation to language children get more optimal. Which more optimally language stimulation getfrom their experience of interaction with their environment, example in the school and home. This researchis using design uses analytic correlation with CrossSectional. Population in this research is all parents andtheir children in Al-fath kindergarten, with totally 200chil, with couple sample get 18 with The samplingtechnique is simple random sampling. As that variable independent is language stimulation getting fromparents. And that variable dependent is Age children of preschool of language growing. This researchinstrument for get language stimulation from parent is using close questioner and growing language is usingform DDST II at sector language, which then result for languagestimulation is 0ften of 77,8%, sometime of22,22%, and It has never of 0%, and result is language of growing is the good of 61,11%, the enough of38,89%, less of 0%. It is got from Gamma correlation with it counting computer program SPSS 12 forwindow G =0.950 with significance level (P) 0.030 andï¡= 5 % or 0,05. This mean there are associationthat more strength stimulation from parent, the better the language of pre-school age-children. Languagestimulation is good, directional and true is important for get guidance early screening language growing soif there are delay can immediately is doing early treatment so that is not influence stage continuedevelopment. So nurse of role is get education from parents are important language stimulation continues inkindergarten and home are need include parents